Kerangka desain untuk mengenerasi continuous connection antara elemen dan peristiwa - Zafira Rahmatul Ummah; Yandi Andri Yatmo; Paramita Atmodiwirjo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
This paper proposes a design framework of Generative Folding as a way to generate continuous connection between architectural elements and events. It argues that Generative Folding has the potential to reveal the complexity of architectural context while also continuously connecting them through proliferative digital tools. The discussion is based on Deleuze’s idea of Fold (1991) and Eisenman’s logic of Object-Event (1993). The folding and alteration of architectural elements produces various connections and continuity between various kinds of time. The article presents a framework development of Generative Folds based on the identification of the relationship of object-event through folding from literature review and the analysis of continuous connection in the precedent of an architectural project by Peter Eisenman. It also discusses the general technical view of Generative Design and how it can expand the exploration of various folds. The findings of this study highlight the potential of further application of Deleuze’s Fold through generative design framework which allows new continuous connections to emerge. The framework becomes the basis for further design development to produce architectural form based on continuous connection.